Reinforcement Learning-Based Tracking Control of USVs in Varying Operational Conditions - Martinsen, Andreas B.; Lekkas, Anastasios M.; Gros, Sébastien; Glomsrud, Jon Arne; Pedersen, Tom Arne (Frontiers in Robotics and AI, 2020)
We present a reinforcement learning-based (RL) control scheme for trajectory tracking of fully-actuated surface vessels. The proposed method learns online both a model-based feedforward controller, as well an optimizing feedback policy in order to follow a desired trajectory under the influence of environmental forces. The method's efficiency is evaluated via simulations and sea trials, with the unmanned surface vehicle (USV) ReVolt performing three different tracking tasks: The four corner DP test, straight-path tracking and curved-path tracking. The results demonstrate the method's ability to accomplish the control objectives and a good agreement between the performance achieved in the Revolt Digital Twin and the sea trials. Finally, we include an section with considerations about assurance for RL-based methods and where our approach stands in terms of the main challenges.